Analisa Perbandingan Metode SAW, WP Dan TOPSIS Dalam Sistem Keputusan - Dendi; Arya Kurniasndi; Muhamad Jukahpin; Fahmi Miftakhul Fuadi; Perani Rosyani (CV. Multi Kreasi Media, 2023)
Decision support system is an arrangement of computer-based information systems that function as decision support in an organization or company. Decision making in determining the provision of financing is very important because with the right decision the provision of financing can be achieved to run well. The decision-making method is useful for determining the best alternative from a number of other alternatives based on certain criteria, including the simple additive weighting method, Weighted Products and Techniques for Order Preference with Similarity to the Ideal Solution. A comparison of the decision support system methods was carried out to determine which method gives the highest value for data accuracy in determining the quality of coffee beans. Based on a comparison of the SAW method, WP and the TOPSIS method, it shows that the weighted product method is more accurate than the simple additive weighting method.